Educational activities of the Ministry of Education during the Iraqi monarchy until 1958 - Assis.Lect. Beidaa Hussein Ibrahim (Journal of College of Education, 2023)
- The research studied (the educational activities of the Ministry of Education during the royal era until 1958), which is considered an important stage in the history of education in the Iraqi districts. These activities focused on clarifying the role of the Ministry of Education in introducing developments and changes in all educational fields, and providing educational services. For the Iraqi brigades
Keywords: educational activities , Ministry of Education , Royal Era